Understanding who cyberloafs from the self-control perspective: a study in the public service sector - Ahmad, Aminah; Omar, Zoharah (Institute of Advanced Science Extension, 2017)
The aim of this study is to understand cyberloafing behavior of employees from the self-control perspective, and to examine differences in cyberloafing according to gender and age, and the gender-age interaction effect. We used survey questionnaires to collect data from 260 Malaysian employees in the public service sector. Our results indicate that the employees engage in cyberloafing with males cyberloafing more than females, irrespective of age. This study contributes to cyberloafing behavior literature by providing an explanation of gender difference in cyberloafing using the self-control theory. The non-significant results on difference in cyberloafing according to age and gender-age interaction effect are discussed. Implications of these results for research and organizational Internet policies and practices are presented.